Novel Forms of Rewriting Aristophanes’ Comedies: Comic Book Adaptations and Their Translations - Lingyu Li; Xiaoli Wang ([sic])
Recent years have witnessed the trend that comedy studies combine with what were once considered separate disciplines, such as translation studies. Nevertheless, few studies have been conducted to investigate the linkages in the areas of comics studies and comedy studies. Rewriting Humour in Comic Books: Cultural Transfer and Translation of Aristophanic Adaptations, which is part of the series of Palgrave Studies in Translating and Interpreting, timely fills the gap by excavating humor in comic book adaptations of Aristophanes’s comedies.The book is composed of six chapters, including an introduction (chapter 1), a main body of 4 chapters, and a conclusion (chapter 6), together constituting a theoretically rich and empirically rigorous study. The first chapter starts by stressing that Marvel Comics may use humor for branding purpose, considering that humor is something memorable that readers are instinctively willing to appreciate and share. The author then explains why he chooses the book adaptations of Aristophanes’s comedies as the prime example of such branding, because the ancient dramaturg’s recognizable name, image, and oeuvre play an indispensable role in the comic books’ popularity. More recently, they have been translated from Greek into four languages, which represent a cultural flow.